2017
DOI: 10.24911/sjp.2017.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the diagnosis and management of Pediatric Rheumatology in the developing world: Lessons from a newly established clinic in Yemen.

Abstract: Pediatric rheumatology is still considered a mysterious branch of pediatric medicine, especially among developing countries. Long-term consequences usually follow delayed diagnosis, referral, and management of rheumatic disorders. We aim to describe the clinical spectrum and the frequency of pediatric rheumatic diseases (PRDs) in AL-Mukalla hospital in Hadhramout province/Yemen. A case record retrospective study was conducted among all patients who attended the pediatric rheumatology clinic in Al-Mukalla hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
(82 reference statements)
1
11
2
Order By: Relevance
“…Consistent with reports from other studies on rheumatic disorders in children joint pain was the most frequent clinical feature noted in this study, musculoskeletal pain was reported in 91.2% of children with rheumatic disorders in Nigeria which is close to our report of 84.6% [8]. Constitutional symptoms also featured in this study and highlighting the importance of considering paediatric rheumatic disorders as possible differentials for children with this presentation [8,15]. Fever was noted as presenting feature in 46% of participants, this might not be attributed entirely to rheumatic conditions, since malaria and other tropical infectious conditions are common in Tanzania.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with reports from other studies on rheumatic disorders in children joint pain was the most frequent clinical feature noted in this study, musculoskeletal pain was reported in 91.2% of children with rheumatic disorders in Nigeria which is close to our report of 84.6% [8]. Constitutional symptoms also featured in this study and highlighting the importance of considering paediatric rheumatic disorders as possible differentials for children with this presentation [8,15]. Fever was noted as presenting feature in 46% of participants, this might not be attributed entirely to rheumatic conditions, since malaria and other tropical infectious conditions are common in Tanzania.…”
Section: Discussionsupporting
confidence: 92%
“…The prescribing and monitoring of biological therapies for children with rheumatic diseases is recommended to be under the supervision of specialists [ 15 17 , 19 ]; therefore, a paucity of specialists is likely a major barrier to access such therapies. Limited access and availability of conventional DMARDs, intraarticular corticosteroids and biological drugs have been reported in other LRIC [ 9 , 26 ]. The important role of the WHO Essential Medicines List (EML) and need to include medicines used in PR care has been highlighted [ 27 ]; revision of the EML is a priority for the PR community to address and if successful, will hopefully improve access to these medicines in many LRIC.…”
Section: Discussionmentioning
confidence: 99%
“…There are severe workforce challenges across the globe but especially so in Asia with one paediatric rheumatologist for every 26 million children [ 2 ]; this contrast markedly with the recommendations for Europe and North America with one paediatric rheumatologist per 0.42 and 0.25 million children respectively [ 2 ]. Although an increase in numbers of rheumatologists and rheumatology trainees were reported [ 5 , 6 ], there were still limited access to paediatric rheumatologists in Southeast Asia [ 7 ]; thus most children with rheumatic diseases were treated mainly by adult rheumatologists and general paediatricians [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Data from Sudan, however, showed a mortality rate of 5.4% among children with rheumatic illness in general. 14 The presence of underlying disease, a heightened inflammatory response, disease and/or drug related organ damage and the possible effect of immunosuppression, in addition to the socioeconomic conditions and incautious health behaviors are all possible factors that might explain the more severe/fatal presentation of COVID-19 among our rheumatic patients. Worth to note that our study relied mostly on their presentation rather than active screening, and thus some milder or asymptomatic cases might have gone unreported or untested, which might have led to overestimation of the morbidity and mortality rates among our series.…”
Section: Methodsmentioning
confidence: 98%
“…For comparing categorical data, Chi-square (X 2 ) test was performed. Exact test was used instead when the expected frequency is less than (10)(11)(12)(13)(14) years. Twenty-nine (59.2%) patients had rheumatologic disease flare at the time of SARS-CoV-2 acquisition while symptoms of the remaining 20 (40.8%) were controlled.…”
Section: Methodsmentioning
confidence: 99%